CORRELATION BETWEEN THE TEST OF 1 MR AND THE EQUATIONS OF MAXIMUM LOAD PREDICTION OF EPLEY AND O'CONNER WITH MEN BETWEEN 20 AND 25 YEARS. (Fiep Bulletin - online, 2014)
The objective of this study was to correlate the found values of maximum load in the test of 1 Maximum Repetition (1 MR), and the equations of Epley and O'Conner. Eighteen men aging between 20 and 25 years practicing weightlifting for at least six months participated the research. Two tests, one of 1 maximum repetition, and other of maximum repetitions had been carried through, within an interval of 48 hours between the tests. In the values of loads found in the test of maximum repetition the equations of Epley and O'Conner's had been applied, the estimate of maximum load was found, was applied a "t" student test for p=0,05, to determine if there was statistical difference among the values of the estimate equations and the test of 1 MR, was also calculated the "r" of Pearson correlation of those samples. These same calculations had been made between the two equations. The results had demonstrated that between the equation of Epley and 1 MR there wasn't significant statistical difference (0,59) and one high correlation (0,98), the same  happening between O'Conner and 1 MR (0.41 and "r" of 0,99), comparing the values of the equations also did not have statistical significant difference (0,18) and one high correlation (0,99). The conclusion for this group is that whether the 1 RM test or any one of the studied equations could be used.
Keywords: maximum strength; 1 MR; maximum load prediction